Peran Guru Kelas Dalam Mengatasi Bullying di Sekolah Dasar Negeri 17 Laman Tanjung Kecamatan Belimbing - Mustakim, Jacky; Mardiana, Mardiana; Susilawati, Indria (STKIP Melawi, 2024)
Abstract: This research is based on the problem of bullying that occurs among students in elementary schools. The aim of the research is to determine the role of class teachers in overcoming bullying behavior and what forms of bullying behavior exist at SD Negeri 17 Laman Tanjung. The research method uses qualitative with a case study approach. This type of research uses descriptive qualitative. Data collection techniques using observation, interviews and documentation. The research instrument used observation sheets and interview sheets. Data analysis techniques include data reduction stages, data presentation and conclusion drawing. Checking the validity of the data uses technical triangulation and source triangulation. The results of research on the role of teachers at SD Negeri 17 Laman Tanjung in overcoming bullying behavior are to become advisors by teaching students not to bully, to be role models such as being an example to students in treating others well, to be mediators such as mediating for students in conflict, become a facilitator by calling students who have problems and provide input and motivation, become an organizer by making school rules by drawing up rules of conduct. The forms of bullying behavior that occur at SD Negeri 17 Laman Tanjung are physical bullying such as throwing stones, hitting and verbal bullying such as making fun of and calling friends with bad names. The conclusion of the research results is that teachers play the role of advisors, role models, mediators, facilitators and organizers in overcoming bullying behavior. The forms of bullying behavior that occur are physical bullying and verbal bullying.Keywords: Role, Class Teacher, BullyingAbstrak: Penelitian ini didasari adanya permasalahan bullying yang terjadi pada siswa di Sekolah Dasar. Tujuan penelitian mengetahui peran guru kelas dalam mengatasi perilaku bullying dan apa saja bentuk perilaku bullying di SD Negeri 17 Laman Tanjung. Metode penelitian menggunakan kualitatif dengan pendekatan studi kasus. Jenis penelitian menggunakan deskriftif kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Instrumen penelitian menggunakan lembar observasi dan lembar wawancara. Teknik analisis data meliputi tahap reduksi data, penyajian data dan penarikan kesimpulan. Pengecekan keabsahan data menggunakan triangulasi teknik dan triangulasi sumber. Hasil penelitian tentang peran guru SD Negeri 17 Laman Tanjung dalam mengatasi perilaku bullying adalah menjadi penasehat dengan mengajarkan kepada siswa tentang tidak boleh melakukan perundungan, menjadi teladan seperti menjadi contoh kepada siswa dalam memperlakukan orang lain dengan baik, menjadi mediator seperti penengah bagi siswa yang berkonflik, menjadi fasilitator dengan memanggil siswa yang bermasalah dan memberikan masukan serta motivasi, menjadi organisator dengan membuat aturan sekolah dengan menyusun tata tertib. Bentuk perilaku bullying yang terjadi di SD Negeri 17 Laman Tanjung adalah bullying fisik seperti melempari, memukul dan bullying verbal seperti mengolok-olok dan menyebut teman dengan julukan yang tidak baik. Kesimpulan hasil penelitian adalah guru berperan menjadi penasehat, teladan, mediator, fasilitator, dan organisator dalam mengatasi perilaku bullying. Bentuk perilaku bullying yang terjadi adalah bullying fisik dan bullying verbal.Kata Kunci: Peran, Guru Kelas, Bullying.